Sub-Nanosecond Greater-Than-10-V Compact Tunable Pulse Generator for Low-Duty-Cycle High-Peak-Power Ultra-Wideband Applications - Renfeng Jin; Subrata Halder; Walter R. Curtice; James C. M. Hwang; Choi L. Law (Active and Passive Electronic Components)
An ultra-wideband pulse generator was designed and fabricated in GaAs HBT IC technology. The generator includes delay and differential circuits to convert a TTL input into a Gaussian pulse signal as well as a Class-C amplifier to boost the pulse amplitude while compressing the pulse width. By adjusting the collector bias of the Class-C amplifier, the pulse amplitude can be varied linearly between 3.5 V and 11.5 V while maintaining the pulse width at 0.3 ± 0.1 nanosecond. Alternatively, by adjusting the base bias of the Class-C amplifier, the pulse width can be varied linearly between 0.25 ns and 0.65 ns while maintaining the pulse amplitude at 10 ± 1 V. Finally, the amplified Gaussian signal can be shaped into a monocycle signal by an L-C derivative circuit. The present pulse generator compares favorably with pulse generators fabricated in CMOS ICs, step-recovery diodes, or other discrete devices.